Nivel de conocimientos, actitudes y prácticas sobre dengue en el asentamiento humano Túpac Amaru, distrito El Porvenir, La Libertad - 2016 - Flores Blancas, Luis Fernando (2018)
To determine the level of Knowledge, Attitudes and Practices regarding dengue of the population of the Tupac Amaru Human Settlement, district of Porvenir, La Libertad, Peru. MATERIALS AND METHODS: Observational, descriptive, cross-sectional study, conducted during December 2016. A structured questionnaire of 28 questions was applied by face-to-face interview method. The data was entered in Microsoft Excel to analyze and obtain graphs and tables. RESULTS: In 232 of the 275 dwellings (84%), a response was obtained. The level of knowledge about dengue was intermediate at 81%, low at 16%, and high at 3% of the population. Attitudes were favorable in 97% and unfavorable in 3% of the population. The population's practices were adequate in 78% and inadequate in 22% of the population. CONCLUSION: The knowledge about dengue in the population of the Tupac Amaru Human Settlement, district of Porvenir, is of intermediate level; the attitudes are favorable; and the practices of the population, adequate